Creativity according to laypeople’s opinions: A transcultural comparison - dos Santos, Marco Antonio (2020)
The conception of creativity may be influenced by laypeople’s opinions and cultural contexts. This study aimed to replicate a study by Bass et al. (2015) with students from the Netherlands about the opinion of facilitating conditions of creativity among lay people, comparing them with Brazilian students. The Brazilian sample consisted of 296 undergraduate students (F = 83%), average age of 24,5 years (SD = 7.73) who did not have any creativity course. The study from the Netherlands consisted of 176 undergraduate students (F = 73.9%) with an average age of 20 years (SD = 5.0). The Brazilian participants answered a questionnaire designed to evaluate the same areas of the Dutch study on situations that favor creativity. The responses compared by t-Student and factor analysis showed differences between countries, with Brazilians giving greater importance to relaxing activities and traveling unlike the Dutch who preferred concentrated activities and being alone. The study concludes that there are cultural influences in the conceptions of creativity.